2021
DOI: 10.3390/nu13041184
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding Is Not Associated with Maternal–Infant Bonding in Early Postpartum, Considering Depression, Anxiety, and Parity

Abstract: It is important to clarify how the breastfeeding method affects women’s mental health, and how women’s mental health affects the breastfeeding method in the early postpartum period when major depression and other psychiatric problems are most likely to occur. This study aimed to examine this bidirectional relationship in the early postpartum period. Participants were 2020 postpartum women who completed the Hospital Anxiety and Depression Scale (HADS) and Mother-to-Infant Bonding Scale (MIBS). We obtained data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…A possible explanation for the difference in results could be that they are limited to a point in the perinatal period, regardless of the pregnancy period. In addition, our ndings demonstrating that anxiety disorders during pregnancy are not signi cantly associated with EBF is consistent with those of previous studies [15,23,24]. However, a North Carolina study reported that anxiety symptoms were associated with earlier introduction of formula supplementation and cessation of breastfeeding [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A possible explanation for the difference in results could be that they are limited to a point in the perinatal period, regardless of the pregnancy period. In addition, our ndings demonstrating that anxiety disorders during pregnancy are not signi cantly associated with EBF is consistent with those of previous studies [15,23,24]. However, a North Carolina study reported that anxiety symptoms were associated with earlier introduction of formula supplementation and cessation of breastfeeding [25].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, our research also indicated that EBF was negatively affected by depression during pregnancy. However, Shari et al [13] and Fukui et al [23] reported that depression was not associated with failure to breastfeed exclusively. A possible explanation for the difference in results could be that they are limited to a point in the perinatal period, regardless of the pregnancy period.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of the Perinatal Mental Health Research Project. [14][15][16][17][18] In this study, we conducted a largescale questionnaire survey in cooperation with the Department of Obstetrics and Gynecology, the Niigata University Medical and Dental Hospital, and 33 associated obstetric institutions in Niigata Prefecture, Japan, between March 2017 and March 2021. We recruited pregnant women, as previously described.…”
Section: Participantsmentioning
confidence: 99%
“…We recruited pregnant women, as previously described. [14][15][16][17][18] In brief, we included pregnant Japanese women aged 18 years or older and excluded those with serious physical complications, serious pregnancy complications, or severe psychiatric disorders (eg, severe schizophrenia or severe depression).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation